Psychotherapy and brain plasticity - Collerton, Daniel (Frontiers in Psychology, 2013)
Purely psychological treatments for emotional distress produce lasting, measureable, and reproducible changes in cognitive and emotional consciousness and brain function. How these changes come about illustrates the interplay between brain and consciousness. Studies of the effects of psychotherapy highlight the holistic nature of consciousness. Pre and post treatment functional Magnetic Resonance Imaging localises the brain changes following psychotherapy to frontal, cingulate, and limbic circuits, but emphasise that these areas support a wide range of conscious experiences. Multivoxel Pattern Analysis of distributed changes in function across these brain areas may be able to provide the ability to distinguish between different states of consciousness.